Reproductive success or failure in four breed groups of beef bulls - Menegassi, Sílvio Renato Oliveira (2015)
The objective of this study was to determine the main causes of failure in bull breeding using a soundness evaluation in Rio Grande do Sul State/Brazil. We evaluated 19,836 bulls from 15 different breeds with ages ranging from two to eight years. The failures of bulls in each step were analyzed by logistic regression. The binary logistic regression was applied because the response variable had only two responses: Success (1) and Failure (0). Older bulls are more likely to be rejected than are younger bulls, regardless of their genetic group. Depending on the step of the assessment, one or another group is rejected. All steps of bull breeding soundness evaluation (BBSE) are important, with special attention to the failures of the behavioral evaluation (libido and physical ability). A BBSE performed before the breeding season reduces the risk of sub-fertile bulls in the herd.